Four newly recorded Amanita taxa from India - YADWINDER SINGH; MUNRUCHI KAUR (Biodiversitas Journal of Biological Diversity, 2016)
Singh Y, Kaur M. 2016. Four newly recorded Amanita taxa from India. Biodiversitas 17: 342-348. During the fungal foraysin district Himachal Pradesh of North Western India, four unrecorded taxa of Amanita were collected. They are Amanita flavoconia var.flavoconia, A. flavoconia var. inquinata, A. pilosella f. pilosella and A. porphyria. A. flavoconia var. flavoconia is distinctive in having abrilliant yellow to yellow orange cap, with white lamellae and a stipe base turning light brownish on injury. Whereas. A. flavoconia var.inquinata possesses brownish orange to yellowish orange to orange yellow, subvicid pileus, having white to pastel yellow stipe, annulusgrayish yellow, superior and volva forming broken rings of yellow patches around the bulb. A. pilosella f. pilosella unique in possessinggrayish brown or brownish beige pileus having thick irregular warts and white lamellae edges. A. porphyria is represented by nonstriatepileus margin, off white stipe, decorated with grayish squamules, with violaceous tinge and has a marginate bulb, annulus is persistent,off white above and light grey below and volva is friable, as grey, cottony mass at the margin of the bulb.